Sports medicine ultrasound (US) beyond the musculoskeletal system: use in the abdomen, solid organs, lung, heart and eye. Issue 3 (10th November 2014) - Berkoff, David J; English, Joy; Theodoro, Daniel
Abstract : The use of point-of-care ultrasound (US) by non-radiologists is not new and the expansion into sports medicine practice is relatively young. US has been used extensively to evaluate the musculoskeletal system including the diagnosis of muscle, tendon and bone injuries. However, as sports medicine practitioners we are responsible for the care of the entire athlete. There are many other non-musculoskeletal applications of US in the evaluation and treatment of the athlete. This paper highlights the use of US in the athlete to diagnose pulmonary, cardiac, solid organ, intra-abdominal and eye injuries.